2020
DOI: 10.1101/2020.09.22.307637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why the COVID-19 pandemic is a traumatic stressor

Abstract: The COVID-19 pandemic does not fit into prevailing Post-traumatic Stress Disorder (PTSD) models, or diagnostic criteria, yet emerging research shows traumatic stress symptoms as a result of this ongoing global stressor. Current pathogenic event models focus on past, and largely direct, trauma exposure to certain kinds of life-threatening events. Nevertheless, among a sample of online participants ( N = 1,040) in five western countries, we found participants had PTSD-like symptoms for events that had not happ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 44 publications
0
61
0
2
Order By: Relevance
“…Given the predominance of convenience samples in the reported studies, it is not possible to reach credible conclusions regarding the prevalence of PTSS in the general population in Croatia or other countries. In addition, given that the COVID‐19 pandemic may not have exposed many individuals to life‐threatening situations or directly exposed them to others’ such experiences, different authors have suggested numerous arguments why COVID‐19‐related stressors should or should not be considered to be potentially traumatic (Bridgland et al., 2020 ; Karatzias et al., 2020 ; Van Overmeire, 2020 ). Despite these disagreements, the fact remains that COVID‐19 provokes the threat of death and causes PTSS in a significant portion of the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the predominance of convenience samples in the reported studies, it is not possible to reach credible conclusions regarding the prevalence of PTSS in the general population in Croatia or other countries. In addition, given that the COVID‐19 pandemic may not have exposed many individuals to life‐threatening situations or directly exposed them to others’ such experiences, different authors have suggested numerous arguments why COVID‐19‐related stressors should or should not be considered to be potentially traumatic (Bridgland et al., 2020 ; Karatzias et al., 2020 ; Van Overmeire, 2020 ). Despite these disagreements, the fact remains that COVID‐19 provokes the threat of death and causes PTSS in a significant portion of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on both past pandemics (Lam et al., 2009 ; Mak et al., 2010 ) and the current COVID‐19 pandemic (Bridgland et al., 2020 ; Karatzias et al., 2020 ; Liu et al., 2020 ; Sun et al., 2020 ) has consistently indicated an increased incidence of PTSS in the population, there have been disagreements regarding whether exposure to COVID‐19 stressors should be considered traumatic stressors consistent with what is required for fulfilling the criteria for the PTSD diagnosis. According to the PTSD diagnosis in the Diagnostic and Statistical Manual of Mental Disorders (fifth ed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple surveys across nations suggest a significant increase in mental health difficulties (CAMH, 2020;Czeisler et al, 2020;Mental Health American, 2020;Statistics Canada, 2020;Xiong et al, 2020) and a recent article by Bridgland et al (2021) suggests that the COVID-19 pandemic is, itself, a traumatic stressor. Among the representative sample of the American population, Czeisler et al (2020) found that 40.9% of respondents reported at least one adverse mental or behavioral health condition, and that 26.3% of the respondents were reporting symptoms of traumatic stress related to the pandemic.…”
Section: Considering the Effects Of A Pandemic On Mental Healthmentioning
confidence: 99%